CEO Compensation and State Ownership in French Listed Companies - Dardour, Ali; Boussaada, Rim (Management international / International Management / Gestiòn Internacional)

(untitled) (HEC Montréal, 2017)
This study investigates the determination of French CEO Compensation. Based on a panel sample of 153 French listed firms between 2003 and 2012, we find U-shaped relationship between State Ownership (SO) and CEO compensation. We attempt to fill the gap of previous French empirical research, which has been limited to cross-sectional studies and has focused on other types of shareholders, using panel data over a period of ten years. The non-monotonic relationship between SO and CEO compensation is initially negative, and then becomes positive with increasing State’s voting rights.